Treatment of petroleum refinery wastewater by an innovative electro-Fenton system: Performance and specific energy consumption evaluation - Marwa M. Jiad; Ali H. Abbar (Case Studies in Chemical and Environmental Engineering, 2023)
The study successfully applied an effective method for removing chemical oxygen demand (COD) from Iraqi petroleum refinery wastewater (PRW) using electro-Fenton (EF) with a new design of electrochemical reactor equipping with a novel cathode design. The study examined the effects of the primary operational parameters, including current density, Fe2+ concentration, and time, on the removal of COD using response surface methodology (RSM). The optimum operating conditions to maximize the COD removal (RE%) and minimize the specific energy consumption (SEC) were found to be a current density of 10.4545 mA/cm2, Fe2+ concentration of 0.50 mM, and a reaction time of 57.57 min, resulting in a RE% of 91.64% with SEC of 5.96 KW h/Kg COD. The study found that the current density had the main impact on RE% followed by Fe2+ concentration and reaction time. The R2 value was (98.53%) demonstrated the successful application of RSM in PRW treatment. The results suggest that the EF process with MPGADC is a promising technology for post-treatment of PRW before final discharge into surrounding water bodies.